The effect of Additional Manalagi (Malus Sylvestris) Apple Cider Juice on Chewy Candy's Sensoric Quality - Farihah Bilqis Safira; Mariani Mariani; Mutiara Dahlia (Green Publisher Indonesia, 2021)
This study aims to study the effect of adding manalagi apple cider to the sensory quality of chewy candy on the aspect of color, taste, aroma, and texture. This research was conducted in the Analysis and Engineering Laboratory of the Culinary Education Study Program Faculty of Engineering State University of Jakarta and was carried out in September 2020. This study uses an experimental method with different percentages namely 20%, 40%, and 60% then a hedonic test is carried out on 15 moderately trained panelists. The results of the descriptive analysis show the average value in the color aspect 4.4 light green categories with a percentage of 40%, in the sweet taste aspect 4.8 categories of sweetness with a percentage of 40%, in the manalagi apple flavor aspect 4.2 feels manalagi apple with a percentage of 40%, in the aspect of manalagi apple aroma 3.9 in the manalagi apple-scented category with a percentage of 40%. Based on the hypothesis test using the Kruskall-Wallis test, it was stated that the texture aspect was continued with the Tuckeys test and the best result obtained was 4.0 which was the best sensory quality product of chewy candy in the addition of Manalagi apple cider.